Risk Management Classification for the Sustainability of Small-scale Dairy Cattle Farming: A Case Study in Suci Village, Jember, Indonesia - Uyun Erma Malika; Huda Ahmad Hudori; Rizal Perlambang CNAW Putra; Budi Prasetyo (Journal of Business Management, 2026)
Sustainable dairy farming plays a critical role in achieving local food self-sufficiency, yet smallholder farmers face multidimensional risks that threaten production and income sustainability. This study aims to classify these sustainability-related risks by applying an Enterprise Risk Management (ERM) framework. Conducted in Suci Village, Jember Regency, Indonesia, this research employed a mixed-method approach combining Focus Group Discussions (FGDs), field observations, and expert validation. Risks were evaluated using a Risk Register matrix based on likelihood and impact. The findings reveal that ecological, economic, social, and technological aspects significantly influence sustainability performance. Ecological risks such as feed shortages, waste pollution, and greenhouse gas emissions were classified as extreme. Economic risks included high feed costs, low milk productivity, and disease outbreaks. Social risks emerged from low farmer income and community conflict due to waste mismanagement, while technological risks were associated with limited cooling systems and low adoption of digital technology. The classification highlights the urgent need for a simplified, community-based risk management system integrating ERM principles for smallholder farmers to enhance resilience and long-term sustainability.